Ta2Ni3Se8: 1D van der Waals Material with Ambipolar Behavior - Choi, Kyung Hwan; Jeong, Byung Joo; Jeon, Jiho; Chung, You Kyoung; Sung, Dongchul; Yoon, Sang Ok; Chae, Sudong; Kim, Bum Jun; Oh, Seungbae; Lee, Sang Hoon; Woo, Chaeheon; Dong, Xue; et al. (Small, 2021)
In this study, high-purity and centimeter-scale bulk Ta2Ni3Se8 crystals are obtained by controlling the growth temperature and stoichiometric ratio between tantalum, nickel, and selenium. It is demonstrated that the bulk Ta2Ni3Se8 crystals could be effectively exfoliated into a few chain-scale nanowires through simple mechanical exfoliation and liquid-phase exfoliation. Also, the calculation of electronic band structures confirms that Ta2Ni3Se8 is a semiconducting material with a small bandgap. A field-effect transistor is successfully fabricated on the mechanically exfoliated Ta2Ni3Se8 nanowires. Transport measurements at room temperature reveal that Ta2Ni3Se8 nanowires exhibit ambipolar semiconducting behavior with maximum mobilities of 20.3 and 3.52 cm2 V−1 s−1 for electrons and holes, respectively. The temperature-dependent transport measurement (from 90 to 295 K) confirms the carrier transport mechanism of Ta2Ni3Se8 nanowires. Based on these characteristics, the obtained 1D vdW material is expected to be a potential candidate for additional 1D materials as channel materials.
Keywords: Carrier transport mechanisms; Electronic band structure; Mechanical exfoliation; Semiconducting behavior; Semiconducting materials; Stoichiometric ratio; Temperature dependent; Transport measurements; 1D van der Waals material; ambipolar behavior; exfoliation; field-effect transistor; indirect-to-direct bandgap transition; synthesis